Selection of Induction Machine Models for Efficiency Evaluation in Electric Vehicles - Aguilera, Facundo (2013)
Different induction machine (IM) models are evaluated, with the aim to determine its usefulness in efficiency studies for electric vehicles (EV) traction drives. In particular, two simple IM models proposed in the literature, which take into account the additional losses, are compared. With this aim, model parameters are adjusted from experimental tests performed on a 4 kW IM. Then, results obtained from both models at different operating points are compared. Even when the estimation errors are similar when using both models, one of them is chosen because of its simplicity. Finally, a simple application of this model is proposed, which consists in use the model for obtaining a complete efficiency map of the IM, without need further essays. Such efficiency map can be used to evaluate the overall efficiency of the traction drive of an EV, or in EV design.